THE INTEGRATED LEARNING OF ENGLISH LANGUAGE USING LIFELONG LEARNING CONCEPT AS A PRACTICAL APPROACH IN ORGANIZATIONS AND COMMUNITIES - Eumgrasamee, Ittivadee; siripukcanun, Niramon (CRMA Journal of Humanities and Social Sciences, 2021)
The purpose of this article was to present the integrated learning of English language using the Lifelong Learning concept as a practical approach in organizations and communities, where the integrated learning of English is becoming essential in modern times. Due to global economic and social competition, English is the primary language of communication. Adult learners in the informal education system have low English language skills, causing problems at work or in communications in trade. It is therefore imperative to develop or establish an English language learning resource, especially in organizations and communities to promote English language learning in this population. As an important concept, Lifelong Learning should be applied in English learning to enable adult learners to achieve self-direction for self-learning and lifelong learning. In this regard, this article aims to present the integrated learning of English language using Lifelong Learning concept as an approach for organizations and communities to establish a systematic process through making available learning resources in organizations and communities, forming cooperative networks, and providing access to English language specialists and Lifelong Learning experts. These resources can promote and develop the English language skills of members of the local communities and allow them to apply their increased English literacy in their daily lives. When people love learning and have developed their own potential to the fullest, they become key figures in driving the nation’s educational and economic system to keep up with global society.